Do Stock Markets move together? - Xu, Nianlong (2012)
In this paper, the purpose of this dissertation is to analyze the co-movements among Chinese, Hong Kong, the United States and Japanese stock market. This dissertation provides evidences to support the hypothesis that there may be long-term benefits for Chinese investors to diversify in the international equity markets. The evidences are based on the data from the stock markets of the United States, Hong Kong, China and Japan over the period of 1st January 2007 to 31st December 2011. Time- series analytical techniques are applied including Granger Causality test and the Vector auto-regression (VAR) model. It is found that the stock markets of both Hong Kong and Japan significantly influence on the Chinese stock market while the United States stock market doesn’t. The correlation between Chinese stock market and the United States stock market is found not strong. However, the results indicate that the impacts from Hong Kong stock market and Japanese stock market on Chinese stock market fade quickly and may not be last in the long run. The results also suggest Japanese stock market has little impact on Chinese stock market compared to Hong Kong. Furthermore, such co-movements phenomenon between the Chinese stock market and the international markets may exist, but not persist in long term. In one word, Chinese stock market seems move together with Hong Kong and Japanese stock market in short term. Therefore, the study suggests that, for Chinese investors’ considerations, it is benefit to diversify across international equity markets. The findings could be contributed reference for Chinese investors who attempt to apply an international diversification strategy while constructing their portfolios.